Possible explanations for an increasing share of no-trip respondents - Christensen, Linda (Proceedings from the Annual Transport Conference at Aalborg University, 2005)
This paper discusses changes in the methodology of The Danish National Travel Survey (DNTS) that could explain some puzzling survey results, such as a 60% increase in the zero trip rate. The DNTS was a continuous survey conducted in the period 1992-2003. In 1998 an unexpected drop in kilometres and number of trips per person was observed, and further discrepancies emerged in the following years until the beginning of 2002. The paper presents an analysis of the changes in the zero trip rate over two periods, from 1997 to 1998 and from 1998 to 2001. For both periods, the explanation is sought in the data collection methodology and not in the changed behaviour of the respondents. The paper shows how sensitive continuous travel surveys are to even minor changes in methodology. It pinpoints the importance of maintaining strictly consistent calling times throughout the week and day. The analysis of the possible explanations for the substantial increase in the zero trip rate shows that the main reason is related to interviewer performance. The importance of keeping a continuous check on interview quality and results cannot be emphasised strongly enough. Furthermore the paper illustrates how the zero trip rate depends on soft refusals and making interviews on cell phones.